Systematic Time Tables – Modelling of Trains’ Paths by Using Genetic Algorithms - Jaromir Siroky (Communications - Scientific letters of the University of Zilina, 2008)
One of construction possibilities of a time table is the implementation of systematic timetabling. In systematic timetabling, the trains’ paths are ordered regularly (thus systematically). In cargo transport there exist a range of possibilities of using an “integrated tact timetable”, which ensures time and space sequences among individual services, forwarders or other kinds of transport. A net-system of service is used in intermodal transport trains, which ensures a net-wide service of each intermodal terminal in the network. The Hub and Spoke system (H&S) is used the most. The intermodal train model of route location in a chosen network is presented in this article. The methods of genetic algorithm were used for finding the result. The modelling of trains’ paths lies in the minimization of intermodal unit transhipment times in intermodal transport ranges.